Comparative study of forecasting methods for energy demand in Morocco. (November 2020) - Nafil, Abdellah; Bouzi, Mostafa; Anoune, Kamal; Ettalabi, Naoufl
Abstract: Nowadays, electricity generation is continuously discussed in climate and environment debates. The energy domain is ever more characterized by a looming exhaustion of fossil fuels (coal, oil, natural gas) and their pernicious environmental repercussions. This is why, finding novel, safe and bountiful energy alternatives is a compelling global matter. Indeed, the ambitious energy strategy adopted in March 2009 aims at reaching a 52% penetration rate of renewable energies by 2030. To reach this purpose, mid-term energy forecasts are prerequisites to have visibility on energy demand growth. This paper contrasts three forecasting methods (ARIMA, Temporal causality modeling, and Exponential smoothing) to calculate the energy demand forecasts of Morocco in 2020. This study seeks to provide more elements to the Moroccan private sector and the government so as to anticipate future consumption and production as scenarios well as plan the necessary investments in the energy sector. Furthermore, this work will inform researchers on the massive integration of renewable energies by providing researchers with a comparative analysis between forecasting methods.